2022
DOI: 10.1155/2022/6666931
|View full text |Cite
|
Sign up to set email alerts
|

Translucency of a Dental Porcelain Mixed by Two Ceramic Slurry Methods: A Bayesian Comparison

Abstract: Background. The ceramics industry produces porcelain pastes using a controlled ratio of water and porcelain powder. Two methods are used to produce a dental porcelain paste: one-step mixing or incremental mixing. Objective. To evaluate the optical properties of a feldspathic dental ceramic using two different ceramic paste preparation methods using a Bayesian approach. Materials and Methods. Two groups of feldspathic porcelain discs, an incremental mixing group (n = 40) and a one-step mixing group (n = 40), we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…It was noticed that increasing the ceramic thickness by the technicians T1 and T2 increased the color difference (∆E) between the target shade (3M2) and the duplicated shade of the specimens, which may be due to poorer ceramic compaction for greater thicknesses. It was observed that these two technicians used a thin ceramic mix with excess water that may evaporate during the firing process, leaving voids acting as scattering centers with a pronounced negative effect at higher ceramic thicknesses [28]. While in the thinner ceramic thickness, the effect of these defects was not as exaggerated as that in thicker sections with accumulated voids.…”
Section: Discussionmentioning
confidence: 99%
“…It was noticed that increasing the ceramic thickness by the technicians T1 and T2 increased the color difference (∆E) between the target shade (3M2) and the duplicated shade of the specimens, which may be due to poorer ceramic compaction for greater thicknesses. It was observed that these two technicians used a thin ceramic mix with excess water that may evaporate during the firing process, leaving voids acting as scattering centers with a pronounced negative effect at higher ceramic thicknesses [28]. While in the thinner ceramic thickness, the effect of these defects was not as exaggerated as that in thicker sections with accumulated voids.…”
Section: Discussionmentioning
confidence: 99%